2013
DOI: 10.1186/2052-3211-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial sensitivity patterns of cerebrospinal fluid (CSF) isolates in Namibia: implications for empirical antibiotic treatment of meningitis

Abstract: ObjectiveBacterial meningitis is a medical emergency associated with high mortality rates. Cerebrospinal fluid (CSF) culture is the “gold standard” for diagnosis of meningitis and it is important to establish the susceptibility of the causative microorganism to rationalize treatment. The Namibia Standard Treatment Guidelines (STGs) recommends initiation of empirical antibiotic treatment in patients with signs and symptoms of meningitis after taking a CSF sample for culture and sensitivity. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
22
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
9
22
3
2
Order By: Relevance
“…Wound biomaterial was the most common source of biomaterial for ESBL producing Enterobacteriaceae isolation in this study, while urine was the most commonly used biomaterial in other studies (Peralta et al, 2012;Kassakian & Mermel, 2014;Moor et al, 2008;Ruiz de Alegría et al, 2011;Kolar et al, 2006). The frequency of other biomaterial for ESBL producing bacteria detection, including abdominal cavity and abscess biomaterial, bronchoalveolar fluid, blood, and cerebrospinal fluid was approximately the same as that described in other literature sources (Peralta et al, 2012;Kassakian & Mermel, 2014;Ruiz de Alegría et al, 2011;Kolar et al, 2006;Mengistu et al, 2013). The frequency of other Enterobacteriaceae found in this study, including P. mirablis, S. marcescens, and K. oxytoca, was similar to that in other studies (Sasirekha, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…Wound biomaterial was the most common source of biomaterial for ESBL producing Enterobacteriaceae isolation in this study, while urine was the most commonly used biomaterial in other studies (Peralta et al, 2012;Kassakian & Mermel, 2014;Moor et al, 2008;Ruiz de Alegría et al, 2011;Kolar et al, 2006). The frequency of other biomaterial for ESBL producing bacteria detection, including abdominal cavity and abscess biomaterial, bronchoalveolar fluid, blood, and cerebrospinal fluid was approximately the same as that described in other literature sources (Peralta et al, 2012;Kassakian & Mermel, 2014;Ruiz de Alegría et al, 2011;Kolar et al, 2006;Mengistu et al, 2013). The frequency of other Enterobacteriaceae found in this study, including P. mirablis, S. marcescens, and K. oxytoca, was similar to that in other studies (Sasirekha, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…This observation corroborate with other studies reporting antimicrobial susceptibility patterns of Gram positive organisms isolated from body fluids. [11,13,15] Overall we observed a general pattern of Gram negative isolates and Enterococci being more commonly isolated from ascitic fluid, while Gram positive isolates were more frequently isolated from CSF and other fluids. This can be explained by the fact that in bacterial peritonitis, there is increased intestinal permeability, which in turn contributes to higher number of enteric pathogens being isolated because of their transmigration across the intestinal wall.…”
Section: Discussionmentioning
confidence: 67%
“…(16). In similar studies from two African countries, Namibia and Ethiopia, reported frequencies are 9.6% and 5.6%, respectively (17,18). This may be a reflection of the different infection control policies and other factors involved in the mentioned regions or countries (19).…”
Section: Discussionmentioning
confidence: 95%